Beam-shaping technique for fiber-coupled diode laser system by homogenizing the beam quality of two laser diode stacks. (March 2020) - Lin, Guyi; Zhao, Pengfei; Dong, Zhiyong; Lin, Xuechun
Highlights: A beam shaping technique is presented to improve the symmetry of the beam quality in both axes. The beam shaping elements are independent of the refractive index of the material. The beam shaping elements are more suitable for high power laser beam shaping. Abstract: A beam shaping technique is presented to homogenize the beam quality of two laser diode stacks. We use polarization beam combiners to halve the beam sizes in the slow axis, and then rearrange the beams coming from two stacks to eliminate the lightless areas by using a quartz-plate stack in the fast axis. By this technique, two 12-bar laser diode stacks are coupled into an 800 µm/0.22 fiber. The experiment shows that the fiber-coupled system has an output power over 1400 W, and the fiber coupling efficiency of 87.5% is achieved, which are almost consistent with the Zemax simulation results.